A naphtha cracking catalyst and its preparation method and application

By crystallizing the MFI structure molecular sieve in situ in an alkaline atmosphere, an efficient naphtha cracking catalyst was prepared, which solved the problem of catalytic performance degradation caused by the binder in the existing catalysts, and achieved high propylene yield and good hydrothermal stability.

CN119746918APending Publication Date: 2025-04-04SHANDONG CHAMBROAD PETROCHEMICALS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411934353.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing naphtha cracking catalysts have problems with degradation of catalytic performance caused by binders and equipment corrosion in catalytic reactions.

Method used

The MFI structural molecular sieve is used as seed crystals and crystallizes in situ in an alkaline atmosphere. The naphtha cracking catalyst is prepared in combination with spray molding and calcining steps to reduce the use of binders and increase the content of the MFI structural molecular sieve.

Benefits of technology

The diene yield, especially propylene yield, is significantly improved in naphtha cracking reaction, and the hydrothermal stability of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211131160000061
    Figure BDA0005211131160000061
  • Figure BDA0005211131160000071
    Figure BDA0005211131160000071
  • Figure BDA0005211131160000072
    Figure BDA0005211131160000072
Patent Text Reader

Abstract

The present invention relates to the field of catalyst technology, and in particular to a naphtha cracking catalyst and a preparation method and application thereof. The preparation method comprises the following steps: a) spraying and molding a mixed solution of a seed, a carrier and a binder and calcining to obtain microspheres; the seed is an MFI structure molecular sieve; b) in-situ crystallizing the microspheres in an alkaline atmosphere to obtain crystallized microspheres; c) calcining the crystallized microspheres to obtain a naphtha cracking catalyst. In the present invention, in a solid phase system, the MFI structure molecular sieve is used as a seed, and in an alkaline atmosphere, a microsphere catalyst containing an active component of the MFI structure molecular sieve is prepared in situ. There is no separation, washing and other operations in the preparation process, no wastewater is generated, and the preparation process is green, clean and harmless. The prepared catalyst has a single composition and mainly contains silicon, aluminum and phosphorus elements. When used in a naphtha cracking reaction, the diene yield, especially the propylene yield, can be greatly improved, and the catalyst has excellent water and heat stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a naphtha cracking catalyst and a preparation method and application thereof. Background Art

[0002] With the increase of economic and consumption levels, people's demand for chemical materials is increasing. The demand for basic chemical raw materials such as ethylene and propylene will continue to maintain a high growth rate. The catalytic cracking process has significant advantages such as deep cracking degree, high olefin yield, co-production of aromatics, low energy consumption (compared to steam cracking), and wide source of raw materials. It is gradually being promoted and applied to produce more low-carbon olefins.

[0003] Catalyst is one of the key research areas in naphtha cracking technology. ZSM-5 molecular sieve is widely used in chemical technology fields such as catalytic cracking and catalytic cracking because of its suitable pore structure, moderate acidity and excellent hydrothermal stability.

[0004] In the fluidized catalyst molding, in order to improve the strength of the molded catalyst, binders such as silica, alumina, aluminum phosphate, etc. are usually added, or acidified pseudo-boehmite is used as a binder. These binders are inert components in the catalytic reaction and will weaken the catalytic performance of the catalyst. In addition, conventional binders need to be added with hydrochloric acid, which will produce acidic gas, and chloride ions will corrode the equipment. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a naphtha cracking catalyst and a preparation method and application thereof, wherein the prepared naphtha cracking catalyst has a higher yield.

[0006] The present invention provides a method for preparing a naphtha cracking catalyst, comprising the following steps:

[0007] a) spraying and calcining a mixed solution of seed crystals, carriers and binders to obtain microspheres; the seed crystals are MFI structure molecular sieves;

[0008] b) in-situ crystallizing the microspheres in an alkaline atmosphere to obtain crystalline microspheres;

[0009] c) calcining the above crystalline microspheres to obtain a naphtha cracking catalyst.

[0010] Optionally, the MFI structured molecular sieve is selected from ZSM-5 molecular sieve.

[0011] Optionally, the carrier includes one or more of silica gel and silica sol.

[0012] Optionally, the binder includes one or more of aluminum sol, silica sol, acidified pseudo-boehmite, and aluminum phosphate sol.

[0013] Optionally, the mass ratio of the seed crystal, the carrier, and the binder is 0.05-0.1:1:0.1-1;

[0014] The solid content of the mixed solution of the seed crystal, the carrier and the binder is 30% to 60%.

[0015] Optionally, the step b) is specifically:

[0016] The microspheres are adsorbed with an alkaline solution until saturated, and the temperature is increased for crystallization, so that the microspheres are crystallized in situ to obtain crystalline microspheres.

[0017] Optionally, the alkaline solution includes one or more of ammonia water, urea, ammonium carbonate, and ammonium bicarbonate;

[0018] The pH of the alkaline solution is 8 to 13;

[0019] The temperature of the heating crystallization is 140-200° C.; the time of the heating crystallization is 12-96 hours.

[0020] Optionally, in the step c), the calcination temperature is 300 to 750° C. and the calcination time is 0.5 to 4 hours.

[0021] The present invention provides a naphtha cracking catalyst prepared by the preparation method, wherein the active component of the naphtha cracking catalyst is an MFI structure molecular sieve.

[0022] The present invention provides a naphtha cracking reaction, which is carried out under the catalytic action of the naphtha cracking catalyst prepared by the above preparation method or the above naphtha cracking catalyst.

[0023] Compared with the prior art, the present invention provides a method for preparing a naphtha cracking catalyst, comprising the following steps: a) spraying and molding a mixed solution of a seed crystal, a carrier, and a binder and calcining to obtain microspheres; the seed crystal is an MFI structure molecular sieve; b) in-situ crystallizing the microspheres in an alkaline atmosphere to obtain crystalline microspheres; c) calcining the crystalline microspheres to obtain a naphtha cracking catalyst.

[0024] The present invention uses an MFI structure molecular sieve as a seed in a solid phase system and in an alkaline atmosphere to in-situ prepare a microsphere catalyst containing an MFI structure molecular sieve active component. No separation, washing and other operations are required in the preparation process, no waste water is generated, and the preparation process is green, clean and harmless. The prepared catalyst has a single composition and mainly contains silicon, aluminum and phosphorus elements. When used in a naphtha cracking reaction, the diene yield, especially the propylene yield, can be greatly improved, and the catalyst has excellent water-resistant and thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1The XRD patterns of the catalysts prepared in the examples and comparative examples are shown in FIG. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a naphtha cracking catalyst, comprising the following steps:

[0027] a) spraying and calcining a mixed solution of seed crystals, carriers and binders to obtain microspheres; the seed crystals are MFI structure molecular sieves;

[0028] b) in-situ crystallizing the microspheres in an alkaline atmosphere to obtain crystalline microspheres;

[0029] c) calcining the above crystalline microspheres to obtain a naphtha cracking catalyst.

[0030] The present invention uses MFI structure molecular sieve as a seed crystal to prepare in situ a microsphere catalyst containing an MFI structure molecular sieve active component in an alkaline atmosphere. When the catalyst is used in a naphtha cracking reaction, the diene yield, especially the propylene yield, can be greatly improved, and the catalyst has excellent water and heat resistance stability.

[0031] The seed crystal may be an MFI structure molecular sieve well known to those skilled in the art, preferably a ZSM-5 molecular sieve.

[0032] The seed crystals may be solid powder or seed crystal solution, preferably solid powder.

[0033] The carrier may be a carrier suitable for microsphere catalysts known to those skilled in the art. In the present invention, the carrier preferably includes one or more of silica gel and silica sol, and more preferably silica gel.

[0034] The binder can be a binder suitable for microsphere catalysts known to those skilled in the art. The present invention preferably includes one or more of aluminum sol, silica sol, acidified pseudo-boehmite, and aluminum phosphate sol, and more preferably, one or more of aluminum sol and silica sol are mixed with aluminum phosphate sol.

[0035] The mass ratio of the seed crystal, the carrier, and the binder is preferably 0.05 to 0.1: 1: 0.1 to 1, and more preferably 0.05 to 0.1: 1: 0.5 to 1. The mass of the binder refers to the mass of the binder oxide.

[0036] The solid content of the mixed solution of the seed crystal, the carrier and the binder is preferably 30% to 60%, more preferably 40% to 50%.

[0037] The mixed solution is preferably an aqueous solution.

[0038] Specifically, the seed crystal, the carrier and the binder are uniformly mixed in water, spray-formed and calcined to obtain the microspheres.

[0039] The calcination temperature is preferably 200-400° C., more preferably 300-350° C.; the calcination time is preferably 0.5-2 h, more preferably 1-2 h.

[0040] The particle size of the microspheres obtained in step a) is 20 to 150 μm, and the particle size distribution meets the requirements of conventional catalytic cracking / cracking.

[0041] Then in situ crystallization is carried out.

[0042] The alkaline atmosphere is preferably provided by one or more of ammonia water, urea, ammonium carbonate and ammonium bicarbonate.

[0043] Preferably, the microspheres are adsorbed with an alkaline solution until saturated, and the temperature is raised for crystallization, so that the microspheres are crystallized in situ to obtain crystalline microspheres.

[0044] The alkaline solution preferably includes one or more of ammonia water, urea, ammonium carbonate, and ammonium bicarbonate; more preferably, it is a mixed solution of one or more of ammonia water and urea.

[0045] The pH of the alkaline solution is preferably 8-13, more preferably 9-12.

[0046] The temperature of the crystallization is preferably 140 to 200° C., more preferably 140 to 180° C.; the time of the crystallization is 12 to 96 hours, more preferably 24 to 72 hours.

[0047] The above-mentioned temperature-raising crystallization is preferably carried out under autogenous pressure and static conditions.

[0048] The autogenous pressure comes from the pressure generated by the alkaline compound when it is heated to become gaseous.

[0049] Preferably, an equal volume of microspheres is immersed in an alkaline solution, and after adsorption saturation, the microspheres are loaded into a reaction kettle and heated for crystallization, so that the microspheres crystallize in situ under autogenous pressure.

[0050] During the above crystallization process, the binder and the carrier crystallize under alkaline atmosphere, seed crystals and autogenous pressure conditions to generate more MFI structured molecular sieves, which not only reduces the amount of binder and reduces the adverse effects of the binder on the catalytic performance, but also increases the amount of MFI structured molecular sieves, thereby increasing the diene yield. The maximum value of the fresh agent reaches 46.2%, and the maximum value of the aged agent reaches 42.3%. Both have abnormally high propylene yields, and the catalyst has high resistance to hydrothermal aging.

[0051] Then the crystalline microspheres are calcined.

[0052] The calcination temperature is preferably 300-750° C., more preferably 300-450° C.; the calcination time is preferably 0.5-4 h, more preferably 1-2 h.

[0053] The calcination is preferably performed in an air atmosphere.

[0054] The present invention provides a naphtha cracking catalyst prepared by the preparation method, wherein the active component of the naphtha cracking catalyst is an MFI structure molecular sieve.

[0055] The naphtha cracking catalyst uses the MFI structure molecular sieve as the active center, has a single composition, and mainly contains silicon, aluminum, and phosphorus elements.

[0056] Preferably, the naphtha cracking catalyst comprises SiO2, Al2O3, and P2O5.

[0057] Preferably, the naphtha cracking catalyst comprises, by oxide mass, 50% to 70% SiO2, 10% to 30% Al2O3, and 5% to 20% P2O5.

[0058] The total content of the above components is 100%.

[0059] The preparation method provided by the present invention does not require separation, washing and other operations during the preparation process, and does not generate wastewater, so the preparation process is green, clean and harmless. When the prepared catalyst is used in a naphtha cracking reaction, it can greatly increase the diene yield, especially the propylene yield, and the catalyst has excellent water-resistant and thermal stability.

[0060] Based on this, the present invention provides a naphtha cracking catalyst prepared by the above preparation method or the use of the above naphtha cracking catalyst as a naphtha cracking reaction catalyst.

[0061] Specifically, the present invention provides a naphtha cracking reaction, which is carried out under the catalytic action of the naphtha cracking catalyst prepared by the above preparation method or the above naphtha cracking catalyst.

[0062] In order to further illustrate the present invention, the following is a detailed description in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0063] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0064] Examples 1-4

[0065] Preparation of microspheres: Deionized water, seed crystals, carriers, and binders were added to the slurry tank in sequence, stirred at high speed, and mixed evenly. The slurry (composition see Table 1) was sprayed to form a fluidized spherical catalyst with a particle size of 20 to 150 microns, and the particle size distribution met the requirements of conventional catalytic cracking / cracking. The microspheres were calcined at 320°C for 1.5 hours to obtain microspheres, which were recorded as: W-1 to 5.

[0066] Equal volume impregnation: Perform equal volume impregnation according to the parameters in Table 2. 1. Test water absorption rate: Take the calcined microspheres, weigh them (M microspheres) and place them in a conical flask, drip deionized water, and stir and vibrate the conical flask with a glass rod until water droplets begin to appear on the inner wall of the flask, and record the dripping mass: M water. Water absorption rate (η) = dripping mass (M water) / catalyst mass (M microspheres). 2. Weigh a certain amount of microspheres M ball 0, calculate the required amount of water according to the water absorption rate (M water 0 = M ball 0 × water absorption rate (η)), dissolve ammonia water and (or) urea in deionized water (M water 0) according to the proportion to form an alkaline solution, drip the alkaline solution into the microspheres under stirring, let it stand for 24 hours, and the impregnation is completed.

[0067] In-situ crystallization: The impregnated microspheres (W-1-4) were loaded into a static reactor, the reactor was sealed, the temperature was raised to 180°C, and the temperature was maintained at autogenous pressure for 48 hours. After the reaction was completed, the microspheres were calcined at 350°C for 1 hour to obtain the catalysts of the present invention, which were recorded as S-1-4.

[0068] Comparative Example 1-2

[0069] Microspheres W-1 and W-2 were directly loaded into a static reactor without impregnation, and the reactor was sealed, heated to 180°C, and kept constant at autogenous pressure for 48 hours. After the reaction, the microspheres were calcined at 350°C for 1 hour to obtain comparative examples 1 and 2, which were recorded as D-1 and D-2, respectively.

[0070] Comparative Example 3

[0071] The impregnated microspheres (W-5) were loaded into a static reactor, the reactor was sealed, the temperature was raised to 180°C, and the temperature was maintained at autogenous pressure for 48 hours. After the reaction was completed, the microspheres were calcined at 350°C for 1 hour to obtain the catalyst of the present invention, which was recorded as D-3.

[0072] Figure 1 : is the XRD pattern of the catalyst prepared in the embodiment and the comparative example. Figure 1 It can be seen that the catalyst prepared in the example has an MFI structure molecular sieve, and the catalysts prepared in comparative examples 1-3 have a lower content of MFI structure molecular sieve.

[0073] Performance test: The performance of the catalyst of the embodiment was tested in a fixed fluidized bed device, and the test conditions were as follows: 1) Catalyst loading: 200 g; 2) Feed rate: 2.0 g / min; 3) Feed time: 10 min; 4) Steam dilution ratio: 1; 5) Reaction temperature: 610°C; 6) Raw material properties (see Table 3). Hydrothermal stability is the stability of the catalyst after aging (at 800°C, 100% steam, space velocity 0.1 h -1 , aging for 20 hours) and then tested.

[0074] Table 1 Composition of the slurry of microspheres used in Examples 1 to 4 (by dry basis)

[0075]

[0076] Table 2 Equal volume impregnation conditions and parameters

[0077]

[0078] Table 3 Physical properties of crude oil

[0079]

[0080] Table 4 Catalytic performance of example samples and comparison agent samples

[0081]

[0082]

[0083] The embodiments and comparative examples all have comparable wear indexes. Among them, the microspheres in comparative examples 1 and 2 did not undergo an impregnation process, and the MFI structure content in the products was only 7.1% and 6.7%, respectively, indicating that the microspheres did not undergo secondary crystallization. In the sample of the embodiment, the MFI structure content increased significantly, reaching a maximum of 64.2%, indicating that the binder and the silica gel carrier crystallized under alkaline atmosphere, seed crystals, and autogenous pressure conditions to generate more MFI structured molecular sieves. In comparative example 3, no seed crystals were added, and no crystallization occurred under alkaline atmosphere and autogenous pressure conditions, and its MFI structured molecular sieve content was close to zero. This conclusion is consistent with the results of the XRD spectrum.

[0084] In terms of catalytic performance, since the catalyst of the embodiment contains more MFI structure molecular sieves, the conversion rate of the embodiment is significantly higher than that of the comparative example. Therefore, the sample of the embodiment has a higher diene yield, the highest value of the fresh catalyst reaches 46.2%, and the highest value of the aged catalyst reaches 42.3%, and both have abnormally high propylene yields. The diene yields of the catalyst of the embodiment after aging decreased by 7.87%, 9.85%, 7.38%, and 8.44%, respectively, while the diene yields of the comparative agent after aging all decreased significantly (the minimum decrease was 23.1%), indicating that the embodiments all have excellent hydrothermal aging resistance.

[0085] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a naphtha cracking catalyst, comprising the following steps: a) spraying and calcining a mixed solution of seed crystals, carriers and binders to obtain microspheres; the seed crystals are MFI structure molecular sieves; b) in-situ crystallizing the microspheres in an alkaline atmosphere to obtain crystalline microspheres; c) calcining the above crystalline microspheres to obtain a naphtha cracking catalyst.

2. The preparation method according to claim 1, characterized in that: The MFI structured molecular sieve is selected from ZSM-5 molecular sieve.

3. The preparation method according to claim 1, characterized in that: The carrier includes one or more of silica gel and silica sol.

4. The preparation method according to claim 1, characterized in that: The binder includes one or more of aluminum sol, silica sol, acidified pseudo-boehmite, and aluminum phosphate sol.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the seed crystal, the carrier, and the binder is 0.05-0.1:1:0.1-1; The solid content of the mixed solution of the seed crystal, the carrier and the binder is 30% to 60%.

6. The preparation method according to claim 1, characterized in that: The step b) is specifically: The microspheres are adsorbed with an alkaline solution until saturated, and the temperature is increased for crystallization, so that the microspheres are crystallized in situ to obtain crystalline microspheres.

7. The preparation method according to claim 6, characterized in that: The alkaline solution includes one or more of ammonia water, urea, ammonium carbonate, and ammonium bicarbonate; The pH of the alkaline solution is 8 to 13; The temperature of the heating crystallization is 140-200° C.; the time of the heating crystallization is 12-96 hours.

8. The preparation method according to claim 1, characterized in that: In the step c), the calcination temperature is 300-750° C. and the calcination time is 0.5-4 hours.

9. The naphtha cracking catalyst prepared by the preparation method according to any one of claims 1 to 8, wherein the active ingredient of the naphtha cracking catalyst is an MFI structure molecular sieve.

10. A naphtha cracking reaction, characterized in that: The method is carried out under the catalytic action of the naphtha cracking catalyst prepared by the preparation method according to any one of claims 1 to 8 or the naphtha cracking catalyst according to claim 9.

Citation Information

Cited By

  • FCC (Fluid Catalytic Cracking) catalyst for maximizing yield of low-carbon olefins as well as preparation method and application of FCC catalyst

    CN121988383A